Brand Experience Analysis of Teh Botol Sosro Consumers Towards the Box Packaging Variant - Rahma Dita Dewayani; Eli Sulihtyaningrum; Asri Annisa Nasution (Jobmark: Journal of Branding and Marketing Communication, 2024)
Teh Botol Sosro is taking steps to vary packaging options by presenting box packaging to remain viable in the Indonesian market. This research looks at the brand experience felt by consumers regarding the packaging variations made by Teh Botol Sosro. Using the case study method with a brand experience theory approach, data were collected through surveys by distributing questionnaires (open questions) and interviews. The research results show that after implementing a packaging variation strategy, the brand experience of Teh Botol Sosro consumers also changes. It was found that sensory consumers get a better experience through more varied packaging designs so they can be customized to meet activity needs, such as being easier to hold. Intellectually, Teh Botol Sosro has succeeded in providing consumers with the latest information in the form of raw materials used for packaging using recyclable paper and still maintaining environmentally friendly glass bottle packaging; behaviorally, consumers do not have to look for a special moment to get Teh Botol Sosro, because whenever and wherever it is relatively easy and practical to find it; Affectionately, the variety of packaging makes consumers feel more connected in various situations while still being able to enjoy Teh Botol Sosro, as is also visualized in several television advertisements.